BIOREMEDIASI TANAH BERTEKSTUR KLEI TERKONTAMINASI MINYAK BUMI: APLIKASI TEKNIK BIOPILE DENGAN PENAMBAHAN PASIR - Arifudin Arifudin; Mohamad Yani; Kukuh Murtilaksono (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Problem encountered in the application of biopile technique for bioremediation of clay textured soils contaminated with crude oil is limited rate of air flow through the soil.  It is a challenge to solve the problem by adding the soil with sand. The addition of sand is also indispensable for the well growth and activity of bacteria in the bioremediation process. This study aims to evaluate the addition of sand on bioremediation of a clay textured soil contaminated with crude oil using biopile technique at pilot scale of 2 tons capacity. The results showed a decline of 76% soil TPH concentration, from 4.22% to 1.00%, within 63 days. Total population of bacteria during the bioremediation process ranged from 1.00 x106 to 1.43 x 1011 CFUs.g-1 soil. At the end of the experiment, a loss in the types and content of some easily degrading  hydrocarbon substances was observed.